The best of both worlds: a Gitxsan seasonal curriculum - Tom, Crystal (Author); Fraser, Tina (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2012)
Statistics reveal that First Nations students in British Columbia have lower school completion rates. First Nations students are becoming lost in the current curriculum and one remedy may be to offer them a more culturally relevant curriculum. In this study, I have developed a Gitxsan seasonal curriculum resource based on the traditional teachings of Elders and knowledge holders as informants. I have worked with five Gitxsan community members chosen for their excellence in traditional knowledge to compile information accessible to First Nations and non-First Nations teachers. I have participated in traditional activities with my informants and recorded informal teaching conversations as content for the resource. The completed resource book corresponds to prescribed learning outcomes for BC schools. I envision that First Nations students whose teachers use this resource will have the best of both worlds, gaining pride in their past and who they are as First Nations people as well as a more confident understanding of where they belong in modern society. --Leaf ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1863086